Superior mesenteric artery syndrome in a neonate: A case report - Takuma Kawawaki; Sachiko Sakai; Yoshihiro Kubota; Masaji Tani (Elsevier, 2024)
Introduction: Superior mesenteric artery syndrome (SMAS) is a complete or incomplete obstruction of the third portion of the duodenum caused by compression between the aorta and the superior mesenteric artery (SMA). Some diagnostic strategies and treatments exist for adults; however, in neonates, these are controversial because the condition is uncommon. Case presentation: A 4-day-old male infant with a birth weight of 2630 g was referred to our hospital with a 2-day history of bilious vomiting. Ultrasonography and contrast enema revealed no malrotation or midgut volvulus. On day 7 of life, an upper gastrointestinal series with contrast revealed obstruction of passage in the third portion of the duodenum. Congenital duodenal stenosis was suspected, and exploratory laparotomy was performed on day 9 of life. The SMA compressed and narrowed the third portion of the duodenum. The duodenum was mobilized and the ligament of Treitz was divided using the technique described by Strong, which released the duodenal compression. A feeding tube was successfully inserted through the duodenum. No duodenal web was observed and SMAS was suspected. The patient's postoperative course was uneventful and SMAS was diagnosed. Complete oral intake was achieved on postoperative day 20, and the patient was discharged on postoperative day 30. Conclusions: Neonatal SMAS is a rare but possible cause of duodenal obstruction. The procedure reported by Strong is useful in neonatal cases.